Spatiotemporal analysis and influencing factors of ecological vulnerability in the Tuojiang River Basin, China - Rui Zhang; Chengyu Hu; Hweesan Lim; Yuanjun Zhang (Geocarto International)
The Tuojiang River Basin, a significant tributary of the upper Yangtze River, serves as a critical ecological barrier and functional zone. Accurately identifying its ecological vulnerability is essential for ecological restoration and regional planning. This study integrates the Vulnerability Scoping Diagram (VSD) framework with the entropy-weighted grey correlation method to develop a region-specific ecological vulnerability assessment system. By quantitatively analyzing spatiotemporal changes in vulnerability from 2000 to 2022, the study reveals the profound impacts of key factors such as topography and land use on vulnerability evolution. Results show that the basin’s ecological vulnerability is predominantly slight to mild, with continuous improvement over the past 22 years. Compared to traditional methods, the proposed multi-model approach is better suited for assessing complex river basin ecosystems. These findings provide innovative insights and scientific support for ecological planning and sustainable development in the Tuojiang River Basin.